Students’ Difficulties in Translating English Short Story into Indonesian at SMP Al-Ulum Terpadu Medan - Arni Mutiara Indah; Yugi Diraga Prawiyata (Education & Learning, 2023)
The study discussed the difficulties of the student in translating the short story from English into Indonesian. The purpose of this study was to know to what extent the students difficulty to translate the short story into Indonesian. The study Uses a Qualitative Descriptive Method. This instrument of study is students translation short story. The study is being conducted at the intermediate school the united Academic Year 2021-2022. The subject of the study taken by four high school students selected by research participants. The criteria of this study the students who had difficulty translating the shory story into Indonesian, The students translation. Students need to translate short stories so we know where their difficulty in translating the short story.